SISTEM PEMASARAN GAMBIR KABUPATEN 50 KOTA - Sari, Fitrah (RC-INSTITUT, 2018)
Gambier is one of specific commodity in Sumatera Barat Province especially in 50 Kota Regency. This product is the specific plant in tropical area with various advantage. The rises of this product still has future chances if seeing at domestic market and export. This study aims to: (1) analyze gambier market structure in gambier marketing 50 Kota Regency, (2) analyze gambier market conduct in gambier marketing 50 Kota Regency, and (3) analyze gambier market performance in gambier marketing 50 Kota Regency. This research was done at January 2013 to August 2013 by using data secondary and primary. The model of analyzing in this gambier marketing by using structure, conduct and performance approach ( SCP method). The result of this research shows that marketing institutions of gambier marketing are farmers trough collecting trader to wholesaler and local exportir for export gambier, whereas marketing institution for pure gambier is farmers to wholesaller and outer of Sumatera Barat Province. Market structure in the research location at collecting trader and wholesaler level is olygopsony, but at exportir level the market structure is monopsony because the point of quality of gambier catechin. Market conduct is seen that farmers spread over at various area with various product, while the gambier end market or the last consumen is far away from production center so bargaining farmers become low. Gambier market performance trough margin and farmer’s share seen that the lowest margin is on pure gambier marketing channel with highest farmer’s share. The other indicator like price transmition elasticity seen that the change of price at exportir unfully to farmers. We can say that gambier marketing in this location research isnot efficient yet and imperfect market. Above condition cause there is no best price for farmers so it impacts to low farmer’s welfare.     Keywords: Gambier, marketing institution, structure-conduct-performance, oligopsony